The effect of gas accretion on the radial gas metallicity profile of simulated galaxies - Collacchioni, Florencia (2020)
We study the effect of the gas accretion rate (M˙ accr) on the radial gas metallicity profile (RMP) of galaxies using the EAGLE cosmological hydrodynamic simulations, focusing on central galaxies of stellar mass M 109 M at z ≤ 1. We find clear relations between M˙ accr and the slope of the RMP (measured within an effective radius), where higher M˙ accr are associated with more negative slopes. The slope of the RMPs depends more strongly on M˙ accr than on stellar mass, star formation rate (SFR), or gas fraction, suggesting M˙ accr to be a more fundamental driver of the RMP slope of galaxies. We find that eliminating the dependence on stellar mass is essential for pinning down the properties that shape the slope of the RMP. Although M˙ accr is the main property modulating the slope of the RMP, we find that it causes other correlations that are more easily testable observationally: At fixed stellar mass, galaxies with more negative RMP slopes tend to have higher gas fractions and SFRs, while galaxies with lower gas fractions and SFRs tend to have flatter metallicity profiles within an effective radius.